Selection for earliness and seed yield in Mung bean accessions using REML/BLUP - Akinyosoye, Solomon Tayo; Agbeleye, Opeyemi Adeola; Adetumbi, Johnson Adedayo; Ukachukwu, Paul Chiedozie (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to select early maturing and high yielding mung bean (Vigna radiata) genotypes for savanna and rainforest conditions in Nigeria. Twenty mung bean genotypes were evaluated, in 2019 and 2020, in the following agroecological zones of Southwestern Nigeria: Rainforest, Derived Savanna, and Southern Guinea Savanna, totaling six environments. The experiment was carried out in a randomized complete block design with three replicates. The restricted maximum likelihood (REML)/best linear unbiased prediction (BLUP) mixed model was used. The magnitude of the phenotypic coefficient of variation was higher than that of the genotypic coefficient of variation for all agronomic characters measured. A high heritability estimate was recorded for first flowering (87%), followed by pod length (85%), number of seeds per pod (79%), and 50% flowering (55%). However, a low heritability was observed for seed yield per hectare (23%). The selective accuracy was 0.5 for yield, which is considered moderate, and ranged from 0.7 to 0.9 for the other characters. A yield of 1,472.93 kg ha-1 was obtained across the six environments. Nine promising genotypes (TVr-45, TVr-98, TVr-64, TVr-102, TVr-86, TVr-106, TVr-9, TVr-95, and TVr-33) were identified. Therefore, these genotypes are suitable and adapted for cultivation in the agroecological zones of Southwestern Nigeria.